Teorias da conspiração: o caso da Covid-19 no Brasil na rede social “X” - Sousa, Renan Silva de (2025)
This thesis aimed to identify and analyze the arguments used by users of "X" (formerly Twitter) during the COVID-19 pandemic regarding vaccination and its side effects. We sought to observe how various descriptions, arguments, and rhetorical devices were mobilized to persuade readers, as well as to construct the identities of adversaries and enemies when arguing about their theories. To this end, we present a body of work composed of three articles. The first article offers a systematic review of studies on conspiracy theories published in the field of psychology between 2009 and 2023. The analysis of the abstracts was conducted with the aid of the IRAMUTEQ software. The results revealed that, in recent years, there has been a significant increase in studies on the topic. This review allowed for an understanding of the academic landscape and the existing gaps in Brazil regarding the subject. The second article seeks, through discourse analysis, to observe the argumentative and rhetorical character employed by conspiracy theorists on the social network "X," that is, to identify the main discursive strategies used to make their discourse convincing and apparently factual. Finally, the third article analyzes the construction of adversary and enemy identities when conspiracy theorists mention their theories on "X." For the latter two articles, the "X" API (Application Programming Interface) was used to select messages that met the defined criteria, followed by the extraction of the data that formed the analyzed corpus. After processing and organizing the data, the requalify.ai software was employed for categorization and coding, leading to the proper analysis. Requalify.ai is an artificial intelligence (AI) software that supports the analysis of qualitative data. Following the initial input — based on the study’s objectives and the key concepts for content recognition by the software — the data were entered monthly, enabling the organization of codes (tags). With the messages coded into thematic categories, analytical questions related to the corpus were developed with the aid of the software's "Q&A" tool, subsequently extracting the messages that would be analyzed discursively. The data analysis was based on the theoretical-methodological framework of Discursive Social Psychology, which understands discourse and language as tools capable of producing, through different actions, the social reality in which we live, including its groups and dynamics. In the second article, it was concluded that conspiracy theorists, when arguing about vaccination, resort to four fundamental categories: (1) vaccination as a mechanism of control; (2) vaccination, hidden and economic interests; (3) origins of the virus, vaccines, and their technologies; and (4) side effects of vaccination. In presenting their positions, conspiracy theorists employ various discursive strategies and rhetorical devices to achieve their goals. In the third article, it was observed that conspiracy theorists focus their criticism on two types of social actors — political and economic actors — for the production of antagonistic identities. These and other findings contribute to understanding the procedures used to make their discourse appear factual, aiming to persuade readers against vaccination and towards unproven alternative treatments. However, due to the group's complexity and its constant transformation and alterity, further studies are recommended to better understand these discursive strategies in other contexts, as well as to identify new adversaries and enemies of their theses.